Fish Intake, Genetic Predisposition to Alzheimer Disease, and Decline in Global Cognition and Memory in 5 Cohorts of Older Persons. Issue 5 (19th October 2017) - Samieri, Cécilia; Morris, Martha-Clare; Bennett, David A; Berr, Claudine; Amouyel, Philippe; Dartigues, Jean-François; Tzourio, Christophe; Chasman, Daniel I; Grodstein, Francine
Abstract: Fish are a primary source of long-chain omega-3 fatty acids, which may help delay cognitive aging. We pooled participants from the French Three-City study and 4 US cohorts (Nurses' Health Study, Women's Health Study, Chicago Health and Aging Project, and Rush Memory and Aging Project) for whom diet and cognitive data were available ( n = 23, 688 white persons, aged ≥65 years, 88% female, baseline year range of 1992–1999, and median follow-up range of 3.9–9.1 years) to investigate the relationship of fish intake to cognitive decline and examine interactions with genes related to Alzheimer disease. We estimated cohort-specific associations between fish and change in composite scores of global cognition and episodic memory using linear mixed models, and we pooled results using inverse-variance weighted meta-analysis. In multivariate analyses, higher fish intake was associated with slower decline in both global cognition and memory ( P for trend ≤ 0.031). Consuming ≥4 servings/week versus <1 serving/week of fish was associated with a lower rate of memory decline: 0.018 (95% confidence interval: 0.004, 0.032) standard units, an effect estimate equivalent to that found for 4 years of age. For global cognition, no comparisons of higher versus low fish intake reached statistical significance. In this meta-analysis, higher fish intake was associated with a lower rate of memory decline. We found no evidence of effect modification by genes associated with Alzheimer disease.